Investigation into the temporal impacts of drought on vegetation dynamics in China during 2000 to 2022 - Yutian Du; Subing Lv; Fuqiang Wang; Jie Xu; Heng Zhao; Lei Tang; Heng Wang; Honglu Zhang (Scientific Reports, 2025)
Abstract Quantifying vegetation’s response to drought and understanding its mechanisms is crucial for mitigating the adverse effects of drought disasters. The asymmetric cumulative and lag effects of drought on vegetation growth are widespread, yet the responses of different vegetation types, climate zones, and elevations in China remain unclear. This study used the Standardized Precipitation Evapotranspiration Index (SPEI) and Normalized Difference Vegetation Index (NDVI) to analyze vegetation status and drought trends from 2000 to 2022, examining the differentiation and mechanisms of cumulative (CED) and lag effect of drought (LED) under various conditions. The main findings are as follows: (1) 85.1% of the study area is becoming greener, with an overall growth rate of 0.026 per decade. Annual drought levels fluctuate, with increasingly severe conditions in parts of southwestern and northwestern China. (2) CED affects 35.94% of vegetated areas, with 77.44% showing a positive correlation between SPEI and NDVI. Grasslands have the longest CED (5.90 months), while forests have the shortest (4.72 months). Temperate and Arid climate zones show higher CED, at 6.91 months and 6.77 months, respectively. The highest CED is found at elevations of 2000–2500 m (6.34 months), and the lowest at 3000–3500 m (4.28 months). (3) LED affects a larger area (39.22%) with an average duration of 6.42 months, greater than the average CED (5.56 months). Grasslands have the longest LED (7.72 months), while forests (6.78 months) and shrublands (6.48 months) are shorter. The Arid climate zone has the highest LED (8.35 months), and the Tropical zone the lowest (4.82 months). LED shows significant elevation differences, being smallest at low elevations (6.48 months). (4) Climate type and potential evapotranspiration explain 0.269 and 0.259 of CED, respectively. For LED, temperature and potential evapotranspiration are dominant (0.173 and 0.167). The combination of factors significantly enhances the explanatory power of temporal effects. (5) NDVI stability is negatively influenced by CED. This study enhances understanding of the vegetation-drought relationship in China and provides theoretical support for addressing drought risks under climate change.